Longitudinal analyses of maternal and cord blood manganese levels and neurodevelopment in children up to 3 years of age: The Japan Environment and Children's Study (JECS). (March 2022) - Yamamoto, Midori; Eguchi, Akifumi; Sakurai, Kenichi; Nakayama, Shoji F.; Sekiyama, Makiko; Mori, Chisato; Kamijima, Michihiro; ,
Graphical abstract: Highlights: Association of maternal/cord blood Mn with child neurodevelopment was examined. Child neurodevelopment was assessed by J-ASQ-3 at 6 months to 3 years. Maternal Mn was negatively associated with gross motor function at almost all ages. Cord blood Mn was negatively associated with gross motor function at 3 time points. Excessive Mn exposure may have adverse effects on neuromotor function. Abstract: Background: Manganese (Mn) is an essential trace metal and a neurotoxicant. Adverse effects of Mn exposure on the neurodevelopment of children have been reported. However, there is limited information on the effects of maternal exposure during pregnancy. Objectives: We aimed to investigate the association between maternal and cord blood Mn levels and neurodevelopment in children aged between 6 months and 3 years using data from a Japanese nationwide birth cohort study. Methods: We used the data of 63, 767 mother–child pairs with maternal blood Mn measurements recorded during the second and third trimester and of 3, 787 mother–child pairs with cord blood Mn measurements. Neurodevelopment was assessed using the Japanese version of the Ages and Stages Questionnaires, third edition (J-ASQ-3), which was completed by parents or guardians at 6 months, 1 year, 1.5 years, 2 years, 2.5 years, and 3 years of age. Results: The median maternal and cord blood Mn levels were 15.2 and 44.5 ng/g, respectively. After adjusting for covariates, both maternal and cord blood Mn levels were negatively associated with J-ASQ-3 scores. Maternal blood Mn levels were negatively associated with gross motor function scores at all ages except for that at 1.5 years (adjusted β: −0.55 to −1.23 for a two-fold increase in maternal Mn levels). The risk of developmental delay (score below the cut-off) in gross motor function increased at the same time points (adjusted odds ratio: 1.08 to 1.13). In the subgroup, cord blood Mn levels were negatively associated with gross motor function scores at 1, 2, and 2.5 years (adjusted β: −1.84 to −3.27). Discussion: Maternal blood Mn levels during pregnancy and cord blood Mn levels were negatively associated with neurodevelopment in children up to 3 years of age. Excessive maternal and fetal exposure to Mn may have adverse effects on neuromotor function in children.